RADEC Learning Model for Grade Three Science Achievement: Model Pembelajaran RADEC untuk Prestasi Ilmu Pengetahuan Alam Kelas Tiga - Mauludhiyah , Hesty; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Improving science learning in elementary schools requires instructional models that activate students and support conceptual understanding. Specific background: Students at SDN Kraton showed low mastery of the life cycle topic due to passive learning and limited engagement. Knowledge gap: Few studies have examined the use of the RADEC model specifically for third-grade science learning on life cycle material using a pre–post experimental design. Aims: This study analyzes the application of the RADEC learning model to improve science learning outcomes in grade three. Results: The research employed a one-group pretest–posttest design involving 28 students. Pretest results showed only 39 percent achieving mastery, while posttest results increased to 71 percent. Statistical analysis using a paired t-test demonstrated significant differences between pretest and posttest scores, indicating that RADEC supports active participation and conceptual understanding of life cycle stages. Novelty: This study provides evidence of RADEC’s effectiveness in lower-grade science learning, particularly on a topic that often presents conceptual difficulties for young learners. Implications: RADEC can serve as an alternative model for elementary science instruction, emphasizing structured reading, discussion, explanation, and creative representation activities. Highlights• RADEC applied to life cycle learning• Improvements in elementary science outcomes• Structured active learning process Keywords: RADEC Model, Science Learning, Elementary Students, Life Cycle, Learning Outcomes